The role of β pockets resulting from Fe impurities in hydride formation in titanium. (May 2022) - Tan, Qing; Yan, Zhiran; Wang, Huijun; Dye, David; Antonov, Stoichko; Gault, Baptiste
Abstract: The corrosion potential of commercially pure titanium in NaCl solutions is dramatically affected by trace Fe additions, which cause the appearance of submicron pockets of β phase at grain boundary triple points. Furthermore, the low solubility of hydrogen in hexagonal close-packed α-Ti makes titanium alloys prone to subsequent hydride-associated failures due to stress corrosion cracking. We analyzed α-α and α-β sections of the abutting grain boundary of a β pocket in a Grade 2 CP-Ti, and the α-β phase boundary. Fe and H partition to β and segregate at the grain boundary, but no segregation is seen at the α-β phase boundary. In contrast, a significant Ni (>1 at%) accumulation is observed at the α-β phase boundary. We propose that the β-pockets act as hydrogen traps and facilitate the nucleation and growth of hydrides along grain boundaries in CP-Ti. Graphical abstract: Image, graphical abstract